(untitled) (Philosophy and Progress, 2025)
This article attempts to revisit the concept of philosophical progress. Is philosophy making progress? If yes, to what extent? In recent times, philosophers have believed a variety of positions regarding the answers to these issues, ranging from the belief that no progress has been made at all, whatsoever others argued that philosophy has addressed every major philosophical questions. These opinions, however, are challenging to analyze and assess, in light of the fact that they are based on different perspectives about the circumstances under which philosophical advancement might occur. Reexamining the concept of philosophical progress is one of its plans. In this article, the following issues will be addressed: firstly, to explain concept of progress in philosophy; secondly, to analyze the debates about the prevalence of philosophical progress; thirdly, to expound three challenges to philosophical progress with special reference to Jessica Wilson; fourthly, resolutions to overcome the philosophical challenges. This article closes with some reflections on philosophical progress in the future. Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 191-208